Effects of Aging Treatment on Laser-Welded Mg-Rare Earth Alloy NZ30K. (24th September 2013) - Dai, Jun; Yang, Li; Li, Lili; Guo, Guolin; Guo, Lanzhong
Abstract : Magnesium-rare earth alloys have received extensive attention due to their attractive mechanical properties resulting from high density of precipitation. The precipitation sequence in laser-welded Mg-3Nd-0.2Zn-0.4Zr (NZ30K) alloy during aging treatment at 200°C and 225°C has been investigated using transmission electron microscopy (TEM). The results indicate that the tensile strength of laser-welded NZ30K can be improved significantly after aging treatment at 200°C for 8 h. It is found that the precipitation in laser-welded NZ30K alloy follows the sequence of supersaturated solid solution → β ′′(DO19 ) → β ′(fcc).